2017
DOI: 10.5194/acp-17-4945-2017
|View full text |Cite
|
Sign up to set email alerts
|

Emissions of volatile organic compounds (VOCs) from concentrated animal feeding operations (CAFOs): chemical compositions and separation of sources

Abstract: Abstract. Concentrated animal feeding operations (CAFOs) emit a large number of volatile organic compounds (VOCs) to the atmosphere. In this study, we conducted mobile laboratory measurements of VOCs, methane (CH 4 ) and ammonia (NH 3 ) downwind of dairy cattle, beef cattle, sheep and chicken CAFO facilities in northeastern Colorado using a hydronium ion time-of-flight chemical-ionization mass spectrometer (H 3 O + ToF-CIMS), which can detect numerous VOCs. Regional measurements of CAFO emissions in northeaste… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(39 citation statements)
references
References 39 publications
1
38
0
Order By: Relevance
“…A few other studies that have apportioned (Peischl et al, 2018;Petron et al, 2014;Townsend-Small et al, 2016) or quantified (Eilerman et al, 2016;Fried et al, 2015;Gilman, 2017;Tzompa-Sosa et al, 2017;Yuan et al, 2017) CH 4 in the DJB study area exist, but none have attempted to source apportion CH 4 based on excess columns. These results can be used to assess how the concept of excess columns compares with results based on in situ observations.…”
Section: Comparison With the Literaturementioning
confidence: 99%
“…A few other studies that have apportioned (Peischl et al, 2018;Petron et al, 2014;Townsend-Small et al, 2016) or quantified (Eilerman et al, 2016;Fried et al, 2015;Gilman, 2017;Tzompa-Sosa et al, 2017;Yuan et al, 2017) CH 4 in the DJB study area exist, but none have attempted to source apportion CH 4 based on excess columns. These results can be used to assess how the concept of excess columns compares with results based on in situ observations.…”
Section: Comparison With the Literaturementioning
confidence: 99%
“…4), although there was higher variability in organic acids and formaldehyde. The highest relative abundances of organic acids were observed in the DenverJulesburg Basin and are likely due to primary emissions from concentrated animal feeding operations and not photochemistry (Eilerman et al, 2016;Yuan et al, 2017). Figure 4 compares the distribution of oxygenates to that measured during the Uintah Basin Winter Ozone Study (UB-WOS) 2013 campaign (Utah Division of Air Quality, 2014), the SENEX and CalNex flights, and the CalNex ground site in Los Angeles (Veres et al, 2011;Warneke et al, 2013).…”
Section: Overview Of H 3 O + Tof-cims Measurementsmentioning
confidence: 99%
“…The ventilation air from animal production facilities contains a variety of chemical compounds, relatively high water content and high densities of particulate matter. This includes a great number of volatile organic compounds (VOCs) that are emitted in agricultural buildings from, e.g., silage, manure and the animals themselves (Feilberg et al, 2010;Hafner et al, 2013;Hansen et al, 2012;Ngwabie et al, 2008;Shaw et al, 2007;Yuan et al, 2017). Several NH 3 analyzers are sensitive to water vapor and other gasses (Bobrutzki et al, 2010;Huszár et al, 2008;Ni and Heber, 2008;Rom and Zhang, 2010;Rosenstock et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In many agricultural emission studies, photoacoustic spectroscopy (PAS) (Poissant et al, 2005;Rom and Zhang, 2010;Saha et al, 2010;Wu et al, 2012;Zhang et al, 2005;Zong et al, 2014) has been used, but findings by Rosenstock et al (2013) and Liu et al (2019) show high interference on NH 3 measurements from a variety of organic compounds including carboxylic acids and alcohols. Hassouna et al (2013) reported nonconstant bias in the results from PAS measurements on NH 3 and N 2 O caused by organic compounds often present at agricultural sites, which makes the PAS measurements unreliable in an agricultural setting.…”
Section: Introductionmentioning
confidence: 99%